2015
DOI: 10.1038/srep10679
|View full text |Cite|
|
Sign up to set email alerts
|

Drosophila Rif1 is an essential gene and controls late developmental events by direct interaction with PP1-87B

Abstract: Rif1, identified as a regulator of telomerase in yeast, is an evolutionarily conserved protein and functions in diverse processes including telomere length regulation, epigenetic gene regulation, anti-checkpoint activity, DNA repair and establishing timing of firing at replication origins. Previously we had identified that all Rif1 homologues have PP1 interacting SILK-RVxF motif. In the present study, we show that Drosophila Rif1 is essential for normal fly development and loss of dRif1 impairs temporal regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 44 publications
6
41
0
Order By: Relevance
“…1E). This observation, together with genetic evidence from yeast 15, 26, 27 and Drosophila 16 , suggests that Rif1 may itself be a regulatory subunit of PP1. To explore this hypothesis, we have further characterized the Rif1-PP1 interaction in molecular detail.
Figure 1Rif1-associated complexes are enriched for chromatin-related proteins and PP1 substrates/regulators.
…”
Section: Resultsmentioning
confidence: 88%
“…1E). This observation, together with genetic evidence from yeast 15, 26, 27 and Drosophila 16 , suggests that Rif1 may itself be a regulatory subunit of PP1. To explore this hypothesis, we have further characterized the Rif1-PP1 interaction in molecular detail.
Figure 1Rif1-associated complexes are enriched for chromatin-related proteins and PP1 substrates/regulators.
…”
Section: Resultsmentioning
confidence: 88%
“…One example where the mitotic surveillance pathway must be inactive is in early mouse embryos, which proliferate in the absence of centrosomes until the 64-cell stage [30], before becoming sensitive to centrosome loss later in development [6]. Additionally, it is clear that the mitotic surveillance pathway is not present in flies, which lack clear 53BP1 and USP28 homologues [31, 32]. Thus, while the spindle assembly checkpoint serves to guard against chromosome segregation errors and is conserved from yeast to humans, the mitotic surveillance pathway may be restricted to vertebrates.…”
Section: Concluding Remarks: a New Mode Of Mitotic Surveillancementioning
confidence: 99%
“…Rif1 is highly conserved in eukaryotes [24, 25] and has more recently been shown to be a regulator of DNA replication initiation in yeast, flies and mammals [2633]. We and others found that Rif1, through its conserved RVxF/SILK motifs, interacts with protein phosphatase 1 (PP1; Glc7 in budding yeast), and that this interaction is crucial for inhibition of replication origin firing by counteracting the activity of the Dbf4-dependent kinase (DDK) [26, 27, 30].…”
Section: Introductionmentioning
confidence: 99%